2002
DOI: 10.1063/1.1461891
|View full text |Cite
|
Sign up to set email alerts
|

Deep levels and trapping mechanisms in chemical vapor deposited diamond

Abstract: Detector-grade undoped chemical vapor deposited ͑CVD͒ diamond samples have been studied with thermally stimulated currents ͑TSC͒ and photoinduced current transient spectroscopy ͑PICTS͒ analyses in the temperature range 300-650 K. Two previously unknown defects have been identified, characterized by activation energies E 1 ϭ1.14 eV and E 2 ϭ1.23 eV, cross sections of about Ϸ10 Ϫ13 cm 2 and concentrations of N t Ϸ10 16 cm Ϫ3. They have been clearly observed by PICTS and isolated in TSC measurements by use of a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
25
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 55 publications
5
25
0
Order By: Relevance
“…A detailed investigation revealed that this dominant feature is due to the emission from different deep levels. 11 At least four components are needed to fit the experimental results. The best fit is obtained using four deep levels ͑Nos.…”
mentioning
confidence: 99%
“…A detailed investigation revealed that this dominant feature is due to the emission from different deep levels. 11 At least four components are needed to fit the experimental results. The best fit is obtained using four deep levels ͑Nos.…”
mentioning
confidence: 99%
“…A wide range of deeper levels has been reported, including Gonon et al 4 and Hearne et al, 5 who reported activation energies of 1.86 and 1.1 eV, respectively, measured using thermally stimulated current technique ͑TSC͒. Bruzzi et al 6 reported a variety of defect levels in electronic-grade polycrystalline CVD diamond, with activation energies in the range 0.3-1.5 eV, observed using both TSC and PICTS. Alpha particle response measurements are a powerful technique to separate the charge transport and carrier lifetimes of electrons and holes.…”
mentioning
confidence: 99%
“…It was shown that an improved stability can be obtained by pre-irradiating the pCVD diamond films with a high fluence of fast neutrons [10], the method was demonstrated capable of improving the performance of low-to-medium crystalline quality pCVD diamond dosimeters to the level of the highest-purity pCVD diamond films [11]. Nonetheless, it is well known that in this high-quality material there is still a significant amount of native deep and shallow defects, which can be active at room temperature for trapping charges, thus affecting the stability of response of the devices [12]. A study recently performed on pCVD detectors based on state of-the-art polycrystalline diamond films demonstrated that this high quality pCVD diamond is still unsuitable for IMRT applications [9].…”
Section: Introductionmentioning
confidence: 99%